Reliability evaluation of distributed system with participation of DG - Phan , Thi Thanh Binh; Le, Hoang Phong (Journal of Technical Education Science, 2010)
This paper chiefly focuses on solving the reliability problem of the distributive system with participation of DG to provide sufficient power. Methods are presented basing on the operation mode of DG: DG operates peaking mode (when electricity price is higher than fuel costs of DG) or standby mode (when electricity price is lower than fuel cost of DG), and reviewing probability of DG in standby mode succeed in staring. Calculating the reliable indices of section in distribution systems such as SIF, ID, MIF, ENS allows us to evaluate the reliability of system as well as the proposed measures to improve that reliability.